The spring 2011 final stratospheric warming above Eureka: anomalous dynamics and chemistry - Adams, C.; Strong, K.; Zhao, X.; Bourassa, A. E.; Daffer, W. H.; Degenstein, D.; Drummond, J. R.; Farahani, E. E.; Fraser, A.; Lloyd, N. D.; Manney, G. L.; McLinden, C. A.; et al. (Atmospheric Chemistry and Physics, 2013)
In spring 2011, the Arctic polar vortex was stronger than in any other year on record. As the polar vortex started to break up in April, ozone and NO2 columns were measured with UV-visible spectrometers above the Polar Environment Atmospheric Research Laboratory (PEARL) in Eureka, Canada (80.05° N, 86.42° W) using the differential optical absorption spectroscopy (DOAS) technique. These ground-based column measurements were complemented by Ozone Monitoring Instrument (OMI) and Optical Spectrograph and Infra-Red Imager System (OSIRIS) satellite measurements, Global Modeling Initiative (GMI) simulations, and meteorological quantities. On 8 April 2011, NO2 columns above PEARL from the DOAS, OMI, and GMI datasets were approximately twice as large as in previous years. On this day, temperatures and ozone volume mixing ratios above Eureka were high, suggesting enhanced chemical production of NO2 from NO. Additionally, GMI NOx (NO + NO2) and N2O fields suggest that downward transport along the vortex edge and horizontal transport from lower latitudes also contributed to the enhanced NO2. The anticyclone that transported lower-latitude NOx above PEARL became frozen-in and persisted in dynamical and GMI N2O fields until the end of the measurement period on 31 May 2011. Ozone isolated within this frozen-in anticyclone (FrIAC) in the middle stratosphere was lost due to reactions with the enhanced NOx. Below the FrIAC (from the tropopause to 700 K), NOx driven ozone loss above Eureka was larger than in previous years, according to GMI monthly average ozone loss rates. Using the passive tracer technique, with passive ozone profiles from the Lagrangian Chemistry and Transport Model, ATLAS, ozone losses since 1 December 2010 were calculated at 600 K. In the air mass that was above Eureka on 20 May 2011, ozone losses reached 4.2 parts per million by volume (ppmv) (58%) and 4.4 ppmv (61%), when calculated using GMI and OSIRIS ozone profiles, respectively. This gas-phase ozone loss led to a more rapid decrease in ozone column amounts above Eureka in April/May 2011 compared with previous years. Ground-based, OMI, and GMI ozone total columns all decreased by more than 100 DU from 15 April to 20 May. Two lows in the ozone columns were also investigated and were attributed to a vortex remnant passing above Eureka at ~500 K on 12/13 May and an ozone mini-hole on 22/23 May.